Predictors of Psychological Well-Being of Nurses and Health Management Specialists - Mamdouh Hajjaj Alrasheedi, Hamdan Rabea Almutrefi, Mohammed Salem Al Rasheedi, Hamdi Hajjaj Al Rasheedi, Fawaz Hajjaj Alrasheedi, Salman Hajjaj Al Rasheedi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Nursing is recognized as a highly stressful profession, with extensive research focusing on sources of job stress and levels of job satisfaction. However, there is a limited number of studies addressing nurses' mental health issues. This study aims to assess the psychological well-being of nurses in various job settings and identify sociodemographic, psychosocial, and workplace predictors of their well-being. A total of 412 nurses from five different health organizations in  participated in the study. A self-administered questionnaire was used to collect sociodemographic, occupational, and health-related data, along with the Standardized Arabic Version of the General Health Questionnaire (GHQ-30 items), Job Descriptive Index (JDI), and Social Support Scale (SSS). The results showed that 21.67% of nurses reported moderate to severe psychological symptoms on the GHQ. Factors such as fewer years of experience, lack of positive family and friend support, and low overall work satisfaction were identified as significant predictors of psychological ill health among nurses, in descending order of importance. The implications of these findings for nursing interventions will be discussed